Plays children love : volume II : a treasury of contemporary & classic plays for children - Harris, Aurand; Jennings, Coleman A., 1933- (New York : St. Martin's Press, 1988)
A collection of nineteen plays to be performed for young audiences or by child actors.
Keywords: Children's plays, American; Plays -- Collections